Ultra-long coherence times amongst room-temperature solid-state spins - Herbschleb, E. D.; Kato, H.; Maruyama, Y.; Danjo, T.; Makino, T.; Yamasaki, S.; Ohki, I.; Hayashi, K.; Morishita, H.; Fujiwara, M.; Mizuochi, N. (Nature communications, 2019)
Solid-state single spins are promising resources for quantum sensing, quantum-information processing and quantum networks, because they are compatible with scalable quantum-device engineering. However, the extension of their coherence times proves challenging. Although enrichment of the spin-zero 12 C and 28 Si isotopes drastically reduces spin-bath decoherence in diamond and silicon, the solid-state environment provides deleterious interactions between the electron spin and the remaining spins of its surrounding. Here we demonstrate, contrary to widespread belief, that an impurity-doped (phosphorus) n-type single-crystal diamond realises remarkably long spin-coherence times. Single electron spins show the longest inhomogeneous spin-dephasing time ( T 2 * ≈ 1.5 ms) and Hahn-echo spin-coherence time ( T 2 ≈ 2.4 ms) ever observed in room-temperature solid-state systems, leading to the best sensitivities. The extension of coherence times in diamond semiconductor may allow for new applications in quantum technology. The coherence times of nitrogen-vacancy centres are key factors influencing their performance in quantum applications. Here the authors show that synthesising phosphorus-doped diamond yields nitrogen-vacancy centres with significantly improved T 2 * and T 2 .